2014
DOI: 10.1111/1471-0528.12756
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of maternal lead levels on birth outcomes in the ALSPAC study: a prospective birth cohort study

Abstract: ObjectiveTo study the associations of prenatal blood lead levels (B-Pb) with pregnancy outcomes in a large cohort of mother–child pairs in the UK.DesignProspective birth cohort study.SettingAvon area of Bristol, UK.PopulationPregnant women enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC).MethodsWhole blood samples were collected and analysed by inductively coupled plasma dynamic reaction cell mass spectrometry (n = 4285). Data collected on the infants included anthropometric variables a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 39 publications
5
73
3
Order By: Relevance
“…22 In other studies, placental lead was negatively associated with gestational age at birth and maternal blood lead was associated with lower birth weight. 23,24 These latter findings are consistent with cohort data demonstrating a higher risk of LBW among women with occupational lead exposure in Norway. 25 Our group recently found that this association was strongest for infants at the lower end of the birth weight-for-gestational-age spectrum, suggesting increased susceptibility to lead among fetuses that were already growing poorly.…”
Section: Environmental Exposuressupporting
confidence: 85%
“…22 In other studies, placental lead was negatively associated with gestational age at birth and maternal blood lead was associated with lower birth weight. 23,24 These latter findings are consistent with cohort data demonstrating a higher risk of LBW among women with occupational lead exposure in Norway. 25 Our group recently found that this association was strongest for infants at the lower end of the birth weight-for-gestational-age spectrum, suggesting increased susceptibility to lead among fetuses that were already growing poorly.…”
Section: Environmental Exposuressupporting
confidence: 85%
“…In a study conducted in Mexico, exposure to lead was assessed during the 1st, 2 nd , and 3 rd trimester in maternal whole blood and plasma and the strongest associations with PTB were seen in early pregnancy (91). Other studies with measures of lead during early pregnancy showed similar results (92, 93). Results from studies assessing lead exposure across pregnancy show less consistent results, with the possibility of lead measurements later in pregnancy attenuating the effect (98, 99).…”
Section: Environmental Chemicals and Ptbsupporting
confidence: 70%
“…The hypothesized mechanisms by which lead can lead to PTB fall into two categories: 1) by influencing hormone levels (91-94) and 2) inducing the production of reactive oxygen species (92, 93). Since the elimination of lead in everyday exposures like fuel and paint, examination of lower levels of lead exposure have become more relevant (95).…”
Section: Environmental Chemicals and Ptbmentioning
confidence: 99%
“…Using linear regression estimates and the international infant growth charts by Fenton et al (Fenton et al 2013), we estimated a decrease in birthweight for a 39-week male infant equal to 10 g per 1µg/dL increase in maternal BLL. Taylor et al showed a comparable decrease in birthweight (13 g per 1 µg/dL increase in maternal BLL) of infants in a UK cohort of 4,285 infants whose mothers had second trimester maternal BLL of 3.67 ± 1.47 µg/dL (mean ± SD) (Taylor et al 2015). Additionally, Zhu et al reported a decrease in birthweight of 4–27 g per 1 µg/dL in a cohort of 43,288 mother-infant pairs in New York, USA, with second trimester maternal BLL of <10 µg/dL (Zhu et al 2010).…”
Section: Discussionmentioning
confidence: 94%